Modulating intestinal immune responses by lipoteichoic acid-deficient Lactobacillus acidophilus - Khan, Mohammad W (2012)
AIM: To investigate the mechanism(s) by which the intestinal commensal microbe Lactobacillus acidophilus can affect host immunity, we studied the role of a component of the cell wall, lipoteichoic acid, in colitis. MATERIALS & METHODS: Colitis was induced by the intraperitoneal injection of pathogenic CD4(+)CD25(−)CD45RB(hi) T cells into Rag1(−/−) mice. The parental strain, NCK56, or the lipoteichoic acid-deficient strain, NCK2025, was then administered orally. Fluorescent microscopy was employed to examine resulting cell populations and their cytokine production in the colon. RESULTS: NCK2025 enhanced IL-10 production by dendritic cells and macrophages. Increased numbers of regulatory dendritic cells coincided with the induction of activated FoxP3(+) Tregs. CONCLUSION: These results suggest that the oral administration of the genetically modified strain NCK2025 may be an effective immunotherapeutic approach that reprograms the immune response in colonic inflammatory conditions.